Fábio Vergara Cerqueira SÓCRATES E O PRAZER - Muniz, Fernando (Mauad X, 2020)
This paper discusses the Socrates' position in relation to pleasure. Was Socrates hedonist or anti-hedonist? This question concerning the historical Socrates doesn't seem to have a definitive answer. But the Platonic Socrates has uncontroversial positions regarding pleasure: at first, he didn't demonstrate particular interest in the subject, but later he rejected hedonism in an emphatic way. What was the motivation for such a development in his perspective? That is the question which constitutes the central theme of this paper.